Design and simulation of an auscultation data acquisition system on a single integrated chip - Kaya, Kerem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2023)
The COVID-19 pandemic has reminded us of the importance of remote healthcare and early detection of symptoms, as most healthcare systems cannot accommodate all patients at once. The burden on health systems can be reduced with smart wearable remote sensing technologies and online health services. This study aims to design a wearable auscultation data acquisition system on a single integrated chip for remote health monitoring. In this study, available auscultation devices, from a conventional stethoscope to multi-channel computerized data acquisition systems, were carefully investigated. The current standard in computerized auscultation data acquisition systems was analyzed and the design choice for a sound acquisition system was presented. The use of low current consuming, high performance MEMS microphone systems has been listed in other wearables in terms of active noise cancellation and as a potential candidate for the proposed low-power wearable auscultation sensor interface. The versatile switched-capacitor-based gain stage and second-order lter design is quickly implemented with Python support. In order to place the other building blocks of the designed new auscultation data acquisition system in a single system, the post-layout simulation of the switched capacitor lter blocks was made using TSMC 180 nm technology, and an important progress is made in development of the proposed system in a single integrated chip.
Keywords: COVID-19 (Disease); Health services administration.